Flawed assumptions used to defend screening mammography. Issue 2 (1st October 2014) - Bleyer, Archie; Thomas, Charles R.; Baines, Cornelia; Miller, Anthony B.
<x xml:space="preserve">Abstract</x> Exaggerating the current benefit of screening mammography and minimizing its harms are readily accomplished by the application of assumptions based on data one‐quarter to half of a century old, and they are neither reliable for predicting what is happening today nor appropriate for the treatment advances that have happened since. Helvie and colleagues are culpable of this conduct.